Improving Psychological Wellbeing and Healthcare Outcomes Through Decentralization of Healthcare Expenditures in Pakistan - Ain, Qurat ul; Xie, Ling; Yousaf, Tahir (Frontiers in Psychology, 2022)
This study has contributed the literature of fiscal decentralization and its impact on the psychological well-being through the investigation of specific hypothesis that explains the improvement in health outcomes due to decentralization of health services. The hypothesis is tested through the application of conventional model of public finance on panel data of health care from 1990 to 2015 across the provinces of Pakistan. The empirical results of the article suggested that the economic reforms in health care sector, through fiscal decentralization in Pakistan, positively impact the public policy effectiveness in improving the health care outcomes over the examined period.